Sediment supply dampens the erosive effects of sea-level rise on reef islands - Megan E. Tuck (Nature Portfolio, 2021)
Abstract Large uncertainty surrounds the future physical stability of low-lying coral reef islands due to a limited understanding of the geomorphic response of islands to changing environmental conditions. Physical and numerical modelling efforts have improved understanding of the modes and styles of island change in response to increasing wave and water level conditions. However, the impact of sediment supply on island morphodynamics has not been addressed and remains poorly understood. Here we present evidence from the first physical modelling experiments to explore the effect of storm-derived sediment supply on the geomorphic response of islands to changes in sea level and energetic wave conditions. Results demonstrate that a sediment supply has a substantial influence on island adjustments in response to sea-level rise, promoting the increase of the elevation of the island while dampening island migration and subaerial volume reduction. The implications of sediment supply are significant as it improves the potential of islands to offset the impacts of future flood events, increasing the future physical persistence of reef islands. Results emphasize the urgent need to incorporate the physical response of islands to both physical and ecological processes in future flood risk models.